EVALUASI PROGRAM INTEGRASI ILMU AGAMA DAN SAINS DI RUMAH PINTAR AL-IKHLAS CABANG SERANG, BANTEN - Aina Rahmatunisa Farhati; Azwina Az-Zahrah; Dewi Utari; Elsa Salsabillah; Novalia Rahmah; Siti Yhunis Arum (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2021)
This study aims to: 1) Determine the effectiveness of the integration program of religion and science which was carried out at the Rumah Pintar Al-Ikhlas Serang Branch. 2) Analyzing the obstacles faced by the Rumah Pintar Al-Ikhlas Serang Branch in implementing this program. 3) Describe the evaluation of the integration of religion and science programs that have been carried out at the Rumah Pintar Al-Ikhlas Serang Branch. This study uses a qualitative approach with descriptive research type and program evaluation using the Tyler model. The results and conclusions of this study are: 1) From the evaluation of the program using the Tyler model in the implementation of the integration program of religion and science at the Rumah Pintar Al-Ikhlas Serang Branch, it was found that the fostered children who took part in this program there were visible changes although not so significant. 2) Obstacles experienced by the Rumah Pintar Al-Ikhlas Serang Branch in implementing this program are the lack of expert teaching staff, teaching media, and the lack of enthusiasm for student learning.